(untitled) (Bangladesh Journal of Plant Taxonomy, 2017)
The types of the names in Bauhinia L. and Phanera Lour. at Central National Herbarium, Howrah (CAL) have been enumerated. Keywords: Fabaceae; Caesalpinioideae; Bauhinia; Phanera; Types; CAL. Bangladesh J. Plant Taxon. 24(1): 18, 2017 (June)